Help the Spanish child refugees! (leaflet)
HELP THE SPANISH CHILD REFUGEES! THIS CHILD REFUGEE FROM SPAIN has lost his home and his parents. His home was bombed to pieces in an air raid. His parents are reported "missing." No one knows whether he will ever see them again. He is just one of thousands of children for whom the Spanish War has meant the destruction of security, health, and all the normal joys of childhood. Shortly after the bombing of Guernica, four thousand Spanish children from the Basque country were brought to Great Britain for safety. More than two thousand of them have since been restored to their parents. The remaining 1,700 how- 292/946/18a/45(i)